Пошаговое объяснение:
Найдите корень уравнения.
1)
9(x-1)=x+15
9x - 9 = x + 15
9x - x = 15 + 9
8x = 24
x = 24 : 8
x = 3
2)
(11x+14)-(5x-8)=25
11x + 14 - 5x + 8 = 25
6x + 22 = 25
6x = 25 - 22
6x = 3
x = 3 : 6
x = 0,5
3)
12-4(x-3)=39-9x
12 - 4x + 12 = 39 - 9x
24 - 4x = 39 - 9x
9x - 4x = 39 - 24
5x = 15
x = 15 : 5
x = 3
4)
2(3x+5)-3(4x-1)=11,8
6x + 10 - 12x + 3 = 11,8
-6x + 13 = 11,8
6x = 13 - 11,8
6x = 1,2
x = 1,2 : 6
x = 0,2
Решите уравнение:
1)
-7(2-3x)=56
-14 + 21x = 56
21x = 56 + 14
21x = 70
x = 70 : 21
x = 3 1/3
2)
(5+7a)*15= -30
75 + 105a = -30
105a = -30 - 75
105a = -105
a = -1
Решите уравнение:
1)
0,4(x-3)-1,6=5(0,1x-0,5)
0,4x - 1,2 - 1,6 = 0,5x - 2,5
0,4x - 2,8 = 0,5x - 2,5
0,5x - 0,4x = -2,8 + 2,5
0,1x = -0,3
x = -0,3 : 0,1
x = -3
2)
1,5(2x-5)+2x=5(0,5x-1,5)-10
3x - 7,5 + 2x = 2,5x - 7,5 - 10
5x - 7,5 = 2,5x - 17,5
5x - 2,5x = -17,5 + 7,5
2,5x = -10
x = -10 : 2,5
x = -4
3)
2/3 (1 1/2x+3/5)-4/5(5/12x-1/2)=1 3/5
x + 2/5 - 1/3x + 2/5 = 1 3/5
2/3x + 4/5 = 1 3/5
2/3x = 1 3/5 - 4/5
2/3x = 4/5
x = 4/5 * 3/2
x = 6/5
x = 1 1/5
Чему равен корень уравнения:
1)
(x-8)/(x+2)=7/3
7*(x+2) = 3*(x-8)
7x + 14 = 3x - 24
7x - 3x = -24 - 14
4x = -38
x = -38 : 4
x = -9 1/2
2)
4/(x-12)=15/(x-10)
15*(x-12) = 4*(x-10)
15x - 180 = 4x - 40
15x - 4x = 180 - 40
11x = 140
x = 140 : 11
x = 12 8/11
б)8x³-11x+8x³-10x³+16x=6х³+5х - степень третья
в)15a⁵+a³-12+2a⁵-a³-30=17а⁵-42 - степень пятая
2.Найдите сумму и разность данных многочленов:
а)(-3ab+6b-3c) + (7ab-6b+2c)=-3ab+6b-3c+7ab-6b+2c=4ab-c
(-3ab+6b-3c) - (7ab-6b+2c)=-3ab+6b-3c-7ab+6b-2c=-10ab+12b-5c
б)(8x²+11x-1) + (3+5x-5x²)=8x² +11x - 1 + 3 + 5x - 5x²= 3x²+16x+2
(8x²+11x-1) - (3+5x-5x²)=8x²+11x - 1 - 3 - 5x + 5x²= 13x² + 6x - 4
3.Докажите тождество.
а)a(b-x)+x(a+b)=b(a+x)
ab - ax + xa + xb = ba + bx
ab + bx = ba + bx
б)16-(a+3)(a+2)=4-(6+a)(a-1)
16 - ( a²+5a+6)=4 - ( 5a+a²-6)
16 - a² - 5a - 6 = 4 - 5a - a² +6
10 - a² - 5a =10 - 5a - a²
4.Решите уравнения:
а)(3x-1)²-9x²=-35
9x²-6x+1-9x²=-35
-6x=-1-35
-6x=-36
x =(-36):(-6)
x= 6
б)4(x-4)(x+8)=(3x+2)(x-5)+(x-1)(x+1)
4(x²+4x-32)=(3x²+13x-10)+(x²-1)
4x²+16x-128 = 3x² +13x -10 +x²-1
16x - 13x =128 -11
3x = 117
x= 117:3
x=39